2013
DOI: 10.1109/lsp.2013.2253550
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic Interference Alignment With Delayed Feedback

Abstract: We propose new ergodic interference alignment techniques for K-user interference channels with delayed feedback. Two delayed feedback scenarios are considered -delayed channel information at transmitter (CIT) and delayed output feedback. It is proved that the proposed techniques achieve total 2K/(K + 2) DoF which is higher than that by the retrospective interference alignment for for the delayed feedback scenarios. Index TermsInterference channel, degrees of freedom (DoF), ergodic interference alignment, delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Reference [39,40] proposed incorporating feedback mechanism in ergodic and retrospective interference alignment algorithm. The feedback mechanism is divided into two kinds: the first is delay channel informational transmitter, referred to as the CIS feedback.…”
Section: A Feedback Mechanismmentioning
confidence: 99%
“…Reference [39,40] proposed incorporating feedback mechanism in ergodic and retrospective interference alignment algorithm. The feedback mechanism is divided into two kinds: the first is delay channel informational transmitter, referred to as the CIS feedback.…”
Section: A Feedback Mechanismmentioning
confidence: 99%
“…The achievable DoF reported in [18] was improved in [19], [20]. Recently, [21] proved the usefulness of ergodic interference alignment in a K-user interference channel when only delayed feedback is available and showed that the sum DoF of 2 can be achievable as K goes to infinity, which is the best DoF result until now in a K-user March 27, 2018 DRAFT interference channel with delayed CSIT. derived in [22]- [24].…”
mentioning
confidence: 95%
“…To align the interference signals in an efficient manner, private information retrieval retrieves the K -user channel values at the receiver side by using databases to recognize the desired message index values [6,7,8,9]. In particular, ergodic IA scheme required past (delayed) channel information (feedback) from the transmitter for effective IA strategies [10]. Authors in [11,12] reported that a dark-blind IA scheme consider staggered antenna switching approach (transmitter equipped with M antennas and K receivers) for vector broadcast channel to solve the interference problems.…”
Section: Introductionmentioning
confidence: 99%